Influence of relationship water/cement upon the processing of cements with pozzolana in standard mortar - Gener Rizo, M.; Álvarez Cabrera, J. L. (Materiales de Construcción, 2002)
The processing of standard mortar is completed following different methods in accordance with the country, but they exist two fundamental tendecies, the ISO and the ASTM. The cuban norm for mechanic-physic tests is based in ISO, and so they use a constant relationship water/cement in the processing of standard mortar a great problem concerning the cement users when they tested those mixed with puzzolanes, because they don’t take care of the bigger water needs of those materials. In this work we present an study of the behaviour of Pozzolanic Portland cements (PP-250) elaborates with a fix and changeable relationship water/cement, obtained starting from the fluidity of the pure Portland cement. (P-350) The results obtained shows that the mechanical resistance decreased in cement mortars PP-250 realised with changeable relationship water/cement. So we recommend the adoption of an optional procedure to elaborate a quality mortar with pozzolana cements.